COVID-19 Pandemic Impacts on Quality of Life of Diabetes Mellitus Patients - Maqfiroch, Arrum Firda Ayu; Gamelia, Elviera; Masfiah, Siti; Rubai, Windri Lesmana (Journal of Public Health for Tropical and Coastal Region, 2024)
AbstractBackground: Diabetes mellitus (DM) is a major concern in the health sector of Indonesia, with more than one million patients. During the COVID-19 pandemic, DM patients have a risk of poor quality of life due to the high potential of fatality from COVID-19 infection or access barriers to health care and nutrition. This study aimed to analyze the impact of the COVID-19 pandemic on the quality of life of patients with diabetes.Methods: This quantitative study used a cross-sectional design. The sampling technique used was total sampling; that is, all members of the population were used as research samples. This research involved 95 patients with DM from 127 total population in Puskesmas Cilongok I. Data were collected through interviews with a guided questionnaire. The data were analyzed using univariate, bivariate, and multivariate analyses.Results: The results of this study indicate that factors related to the quality of life of patients with DM have a pandemic economic impact (p = 0.011 and OR = 0.341), and factors that affect the quality of life of patients with DM have a pandemic economic impact (OR = 0.326). Factors related to poor diabetes patients include losting work, decreased partial or total income, and increased daily expenditure.Conclusion: We suggest that health agencies can help patients with DM restore their quality of life after being hardly affected by the pandemic in the economic aspect by designing a sustainable program for patients with DM.